Self-healing ceria-modified coating for corrosion protection of AZ31 magnesium alloy. (September 2018) - Calado, Lénia M.; Taryba, Maryna G.; Carmezim, Maria J.; Montemor, M. Fátima
Graphical abstract: Highlights: Modification of hybrid epoxy-silane coating with ceria nanoparticles Ceria leads to improved and stable corrosion protection of AZ31 Delay of corrosion propagation in the presence of ceria Enhanced corrosion protection with low concentration of ceria nanoparticles Abstract: A hybrid siloxane-based coating was modified with CeO2 nanoparticles and applied on AZ31. The corrosion protection performance was evaluated via Electrochemical Impedance Spectroscopy (EIS) in 0.05 M NaCl. CeO2 -modified coating showed improved and more stable protective performance compared to the blank coating. Localized healing of the modified coating was studied via Scanning Vibrating Electrode Technique (SVET), Scanning Ion-Selective Electrode Technique (SIET) and Localized Electrochemical Impedance Spectroscopy (LEIS). Addition of ceria led to lower cathodic activity in 0.05 M NaCl and alkalization was kept localized. The CeO2 -modified coating provided corrosion protection, including pre-emptive healing of localized corrosion activity, of AZ31.